Intervenção didático- fonética no ensino do sistema sonoro da língua francesa para falantes nativos de português brasileiro: as vogais anteriores arredondadas - Erica Sarsur Camara (2016)
This research is inserted within the context of phonetic studies and foreign language teaching and focuses on the perception by Brazilian Portuguese native speakers of the French front rounded vowels sounds. The initial reason and work proposal are geared towards teachingforeign languages sounds that are not present in the learners native language. It is assume that a small attention is given to the pronunciation in the early stages of the foreign language studies. Thus, the description of French phonetic modes, the notion of acceptable pronunciation, the elements of corrective phonetic, and the studies of speech perceptionformed the theoretical foundation for the data analysis. The hypothesis of this research is that a phonetic oriented intervention to the production of specific sounds of a foreign language may help to develop the perception of those sounds by the learner. This study aims, therefore, to test the effectiveness of such intervention. In this regard, we undertook two soundperception tests, on which the participants pointed out whether they were listening or not to a specific sound present in the Brazilian Portuguese sound repertoire. As a stimulus, the task uses a continuum of isolated vowel sounds throughout nine stages between [i-y], [e-ø], [-].The experiential informant group was then submitted to a idactic-phonetic intervention in the interval between tests. The results seemed to confirm the hypothesis considering that in the post-test data the majority of the participants showed impressive changes, which could beinferred by the results displayed in a curve of approximate answers to an enlarged Z. This indicates a categorical perception of French sound analyzed in the intervention. The possible contribution of this study to the foreign language teaching relies on the demonstration of the impact of a didactic oriented intervention to teach pronunciation, making use of activities that shall promote sounds production.